Hubungan Pengetahuan dengan Sikap Perawat tentang Triage di IGD Dimasa Pandemi Covid-19 - Siska Evi Martina; Galih Satria; Donal Nababan; Rumondang Gultom (Faletehan Health Journal, 2021)
The number of patients who come to the emergency department makes nurses have to sort patients quickly and precisely according to priority. It requires knowledge and attitude in terms of segregation of patient type and emergency in triage, so that patient care can be more optimal and directed. This study aimed to find out the correlation between nurses’ knowledge and attitudes of triage. The research used a correlation research method with a cross-sectional approach. The study was carried out at the emergency room of Dr. H Kumpulan Pane General Hospital in Tebing Tinggi City, Rantau Prapat General Hospital, and Tuan Rondahaim Simalungun General Hospital from January to August 2020. The samples of this study were 46 nurses in charge at the emergency room of Dr. H Kumpulan Pane General Hospital in Tebing Tinggi City, Rantau Prapat General Hospital, and Tuan Rondahaim Simalungun General Hospital, taken by total sampling. The research instrument was a questionnaire. The data analysis used Spearman’s rank correlation at the 95% confidence interval. The results of the descriptive analysis showed that majority of nurses had adequate knowledge of triage (48%) and majority nurses had positive attitude (77%). The results of Spearman’s rank statistical analysis obtained a spearman correlation coefficient of 0.753 with ρ-value 0.000 < 0.05; thus, Ha was accepted. In conclusion, there is a correlation between nurses’ knowledge and attitude of triage at Dr. H Kumpulan Pane General Hospital in Tebing Tinggi City, Rantau Prapat General Hospital, and Tuan Rondahaim Simalungun General Hospital.